Managing organizational legitimacy: a case for waste management companies in Malaysia / Nor Farhana Mohamad Hafidz, Mahadir Ladisma and Thenmolli Vadeveloo - Mohamad Hafidz, Nor Farhana; Ladisma, Mahadir; Vadeveloo, Thenmolli (Universiti Teknologi MARA, 2020)
Waste management is an essential part of any nation to ensure environmental sustainability. However, due to rapid urbanization and growth of population, the nation still struggles to execute proper waste management practices due to underlying problems such as limited information on proper waste management and recycling as well as unsystematic analysis and subpar documentation. Waste management companies have an obligation to rectify said issues by emphasizing and managing legitimacy to increase their accountability and improve their level of services. Organizational legitimacy is a tool that enables waste management organizations to ensure that the organizational objectives are in congruence with the social values, beliefs, and norms to inculcate green behavior. This study is non-empirical based and reviews past and current literature of legitimacy and ways that organizations manage it. This conceptual paper aims to address how managing organizational legitimacy enables better waste management performance through two approaches, namely the strategic and institutional approach. The analysis of these approaches is hoped to assist waste management organizations to effectively implement their services aside from producing an environmentally conscious society that practices sustainable behaviour.